Positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing positive electrode active material for nonaqueous electrolyte

By using lithium transition metal composite oxides with specific content and structure in the positive electrode active substance of the nonaqueous electrolyte secondary battery, the side reaction problems caused by high Ni content are solved, and the safety and stability of the battery are significantly improved.

CN119404336APending Publication Date: 2025-02-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047007.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-16
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Lithium transition metal composite oxides with a Ni content rate of more than 75% are prone to side reactions in non-aqueous electrolytes, resulting in a large amount of Li captured and the layered crystal structure is easily destroyed, which in turn affects the safety of the battery.

Method used

Using lithium transition metal composite oxides containing Ni, Mn, P, Me, Ca and Sr, by adjusting element content and structural parameters, such as the ratio of Co content to Mn content and the half-value width of the X-ray diffraction spectrum to stabilize the crystal structure and suppress side reactions.

Benefits of technology

It effectively improves the safety of nonaqueous electrolyte secondary batteries, especially under high temperature conditions, reduces the occurrence of self-exothermic reactions and improves the stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404336A_ABST
    Figure CN119404336A_ABST
Patent Text Reader

Abstract

Provided is a positive electrode active material which contributes to improving the safety of a secondary battery. The positive electrode active material contained in the nonaqueous electrolyte secondary battery contains a lithium transition metal composite oxide, and the lithium transition metal composite oxide contains Ni, Mn, P, Me (Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W, and Bi) and at least one of Ca and Sr at a predetermined content ratio. The ratio (m / n) of the half-width (m) of the diffraction peak of the (003) plane to the half-width (n) of the diffraction peak of the (110) plane in an X-ray diffraction pattern based on X-ray diffraction satisfies 0.75 < = m / n.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, a method for producing the positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. Background Art

[0002] It has long been known that lithium nickel oxide (LiNiO2) has a high energy density, and battery characteristics such as reliability can be improved by replacing part of Ni with Co, Al, Mn, etc.

[0003] Patent Document 1 discloses a positive electrode active material having an oxide coating layer containing Li3PO4 formed on the surface of a lithium transition metal composite oxide containing Ni, Mn, Co and Sr. Patent Document 1 states that the use of the positive electrode active material improves the charge and discharge cycle characteristics of a secondary battery.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 6749973 Summary of the invention

[0007] However, lithium transition metal composite oxides with a Ni content of more than 75% are prone to side reactions with non-aqueous electrolytes, and further, the amount of Li captured during charging is large, so the layered crystal structure is easily destroyed. When the temperature in the battery rises due to overcharging, short circuit, etc., a further chemical reaction (self-exothermic reaction) with heat release in the battery as the temperature rises is carried out, and the safety of the battery is sometimes reduced. The technology described in Patent Document 1 has not studied the improvement of the safety of the battery, and there is still room for improvement.

[0008] An object of the present disclosure is to provide a positive electrode active material that contributes to improving the safety of a non-aqueous electrolyte secondary battery.

[0009] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure is characterized by containing a lithium transition metal composite oxide, the lithium transition metal composite oxide containing Ni, Mn, P, Me (Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W, and Bi), and containing at least any one of Ca and Sr. The Ni content rate in the lithium transition metal composite oxide is 75 mol% ≤ Ni content rate < 95 mol% with respect to the total molar number of metal elements other than Li, the Mn content rate in the lithium transition metal composite oxide is 0 mol% < Mn content rate ≤ 20 mol% with respect to the total molar number of metal elements other than Li, the P content rate in the lithium transition metal composite oxide is 0 mol% < P content rate ≤ 2 mol% with respect to the total molar number of metal elements other than Li, the Me content rate in the lithium transition metal composite oxide is 0 mol% < Me content rate ≤ 20 mol% with respect to the total molar number of metal elements other than Li, the total of the Ca content rate and the Sr content rate in the lithium transition metal composite oxide is 0 mol% < Ca content rate + Sr content rate ≤ 2 mol% with respect to the total molar number of metal elements other than Li, the ratio of the Co content rate to the Mn content rate is 0 ≤ Co content rate / Mn content rate < 2, and the ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (110) plane in the X-ray diffraction pattern based on X-ray diffraction is 0.75 ≤ m / n.

[0010] The manufacturing method of the positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure is characterized by including the following steps: a step of mixing at least a metal oxide containing Ni with a Li raw material, a P raw material, and at least one of a Ca raw material and a Sr raw material to obtain a mixture; and a step of firing the mixture.

[0011] The non-aqueous electrolyte secondary battery according to one aspect of the present disclosure is characterized by including: a positive electrode, a negative electrode, and a non-aqueous electrolyte, the positive electrode containing the above positive electrode active material for a non-aqueous electrolyte secondary battery.

[0012] According to the positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure, the safety of the secondary battery is improved, particularly the safety of the secondary battery at high temperatures. In addition, according to the manufacturing method of the positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure, the positive electrode active material for a non-aqueous electrolyte secondary battery can be produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a longitudinal sectional view of a non-aqueous electrolyte secondary battery as an example of an embodiment. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0014] In the layered structure of the lithium transition metal composite oxide, there are transition metal layers such as Ni and Li layers, and the Li ions present in the Li layer reversibly enter and exit, so that the charge and discharge reaction of the battery proceeds. Generally, lithium transition metal composite oxides with Ni as the main component are known as high-capacity positive electrode active materials. However, lithium transition metal composite oxides with a Ni content of more than 80% are prone to side reactions with non-aqueous electrolytes, and further, the amount of Li captured during charging is large, so the layered crystal structure is easily disintegrated due to repeated charge and discharge. Therefore, when the temperature in the battery rises due to overcharging, short circuit, etc., a further chemical reaction (self-exothermic reaction) accompanied by heat release in the battery proceeds as the temperature rises, which may cause the safety valve of the battery described later to work.

[0015] Patent Document 1 discloses a positive electrode active material having an oxide coating layer containing Li3PO4 formed on the surface of a lithium transition metal composite oxide containing Ni, Mn, Co and Sr from the viewpoint of improving charge and discharge cycle characteristics. However, Patent Document 1 does not study the improvement of battery safety.

[0016] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that the safety of the battery is improved by including a lithium transition metal composite oxide containing Ni, Mn, P, Me (Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W and Bi) and at least one of Ca and Sr in a predetermined content ratio in the positive electrode active material, and the ratio of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (110) plane based on X-ray diffraction is 0.75≤m / n. According to the synergistic effect of at least one of Ca and Sr and P, the side reaction with the non-aqueous electrolyte is suppressed, and the crystal structure can be stabilized by making the ratio of the half-value width within a limited range. It is inferred that according to these synergistic effects, the self-exothermic reaction of the battery is suppressed, and the safety of the battery can be improved.

[0017] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention is described in detail. Hereinafter, a cylindrical battery in which a wound electrode body is accommodated in a cylindrical outer shell is exemplified, but the electrode body is not limited to the wound type, and may also be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one through a separator. In addition, the outer shell is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, etc., or may be a battery shell composed of a laminate sheet including a metal layer and a resin layer.

[0018] Figure 1FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. Figure 1 As shown, the secondary battery 10 comprises: a wound electrode body 14, an electrolyte, and an outer case 16 for accommodating the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer case 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the outer case 16 is blocked by a sealing body 17. In the following, for the sake of convenience of description, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the outer case 16 is regarded as the lower side.

[0019] The positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14 are all rectangular strips, and are alternately stacked along the radial direction of the electrode body 14 by spirally winding along the length direction. The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. The negative electrode 12 is formed to be one size larger than the positive electrode 11 to prevent lithium precipitation. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. Two separators 13 are formed to be at least one size larger than the positive electrode 11, for example, arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 includes a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 is the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 is the axial direction. That is, the end faces of the positive electrode 11 and the negative electrode 12 in the width direction form the end faces of the electrode body 14 in the axial direction.

[0020] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer shell 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer shell 16 by welding or the like, and the outer shell 16 serves as the negative terminal.

[0021] A gasket 28 is provided between the outer shell 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer shell 16, with a portion of the side portion bulging inwardly for supporting the sealing body 17. The groove portion 22 is preferably formed in a ring shape along the circumferential direction of the outer shell 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer shell 16 by the groove portion 22 and the open end of the outer shell 16 that is tightly fitted to the sealing body 17.

[0022] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0023] Hereinafter, the positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the secondary battery 10 , particularly the positive electrode 11 , will be described in detail.

[0024] [positive electrode]

[0025] The positive electrode 11 includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, or a thin film having the metal disposed on the surface. The thickness of the positive electrode current collector is, for example, 10 μm to 30 μm.

[0026] The positive electrode mixture layer includes, for example, a positive electrode active material, a conductive agent, and a binder. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm on one side of the positive electrode collector. The positive electrode 11 can be manufactured, for example, as follows: a positive electrode mixture slurry including a positive electrode active material, a conductive agent, etc. is applied to the surface of the positive electrode collector, and after the coating is dried, it is rolled to form a positive electrode mixture layer on both sides of the positive electrode collector, thereby being manufactured.

[0027] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbonaceous particles, etc. These may be used alone or in combination of two or more.

[0028] As the binder contained in the positive electrode mixture layer, for example, fluorine resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide resins, acrylic resins, polyolefin resins, polyacrylonitrile (PAN), etc. can be cited. These can be used alone or in combination of two or more.

[0029] The positive electrode active material contained in the positive electrode mixture layer includes a lithium transition metal composite oxide. The lithium transition metal composite oxide contains Ni, Mn, P, Me (Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W, and Bi), and contains at least any one of Ca and Sr.

[0030] The Ni content rate in the lithium transition metal composite oxide is 75 mol% ≤ Ni content rate ≤ 95 mol% relative to the total molar number of metal elements other than Li. From the viewpoint of achieving both high capacity and structural stabilization, the Ni content rate is preferably within this range. The lower limit value of the Ni content rate is preferably 80 mol%, more preferably 85 mol%.

[0031] The Mn content rate in the lithium transition metal composite oxide is 0 mol% < Mn content rate ≤ 20 mol% relative to the total molar number of metal elements other than Li. From the viewpoint of achieving both high capacity and safety, the Mn content rate is preferably within this range. The lower limit value of the Mn content rate is, for example, 1 mol%.

[0032] The P content rate in the lithium transition metal composite oxide is 0 mol% < P content rate ≤ 2 mol% relative to the total molar number of metal elements other than Li. By making P with this content rate coexist with Ca and Sr, the safety of the lithium transition metal composite oxide can be improved. The lower limit value of the P content rate is, for example, 0.01 mol%.

[0033] The Me content rate in the lithium transition metal composite oxide is 0 mol% < Me content rate ≤ 20 mol% relative to the total molar number of metal elements other than Li. From the viewpoint of achieving both high capacity and structural stabilization, the Me content rate is preferably within this range. The lower limit value of the Me content rate is, for example, 1 mol%.

[0034] The total of the Ca content rate and the Sr content rate in the lithium transition metal composite oxide is 0 mol% < Ca content rate + Sr content rate ≤ 2 mol% relative to the total molar number of metal elements other than Li. By making at least any one of Ca and Sr with this content rate coexist with P, the safety of the lithium transition metal composite oxide can be improved. The lower limit value of the total of the Ca content rate and the Sr content rate is, for example, 0.01 mol%.

[0035] The lithium transition metal composite oxide preferably contains both Ca and Sr. Thereby, the safety of the lithium transition metal composite oxide can be significantly improved.

[0036] The lithium transition metal composite oxide preferably satisfies Ca content rate > Sr content rate. Thereby, the safety of the lithium transition metal composite oxide can be significantly improved.

[0037] The lithium transition metal composite oxide is, for example, a composite oxide represented by the general formula Li a Ni x Mn y P z Me w Ca s Sr t O 2-b (wherein 0.8 ≤ a ≤ 1.2, 0.75 ≤ x ≤ 0.95, 0 < y ≤ 0.20, 0 < z ≤ 0.02, 0 < w ≤ 0.20, 0 < s + t ≤ 0.02, 0 ≤ b ≤ 0.05, x + y + z + w + s + t = 1, and Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W, and Bi). The ratio of the metal elements contained in the lithium transition metal composite oxide can be measured, for example, using an inductively coupled plasma atomic emission spectrometer (ICP-AES).

[0038] In the lithium transition metal composite oxide, the ratio of the Co content to the Mn content is 0 ≤ Co content / Mn content < 2. The upper limit value of the Co content / Mn content is, for example, 1.8.

[0039] In the X-ray diffraction pattern of the lithium transition metal composite oxide, the ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (110) plane is 0.75 ≤ m / n. When m / n is less than 0.75, the strain of the layered structure is too large and the layered structure becomes brittle. The upper limit value of m / n is, for example, 0.85. When m / n exceeds 0.85, the battery capacity may sometimes decrease.

[0040] The X-ray diffraction pattern is obtained by powder X-ray diffraction using a powder X-ray diffractometer (manufactured by Rigaku Corporation, trade name “RINT-TTR”, radiation source Cu-Kα) under the following conditions.

[0041] Measurement range: 15 - 120°

[0042] Scanning speed: 4° / minute

[0043] Analysis range: 30 - 120°

[0044] Background: B-spline

[0045] Curve function: Split pseudo-Voigt function

[0046] Constraint condition: Li(3a) + Ni(3a) = 1

[0047] Ni(3a)+Ni(3b)=α (α is the Ni content ratio of each)

[0048] ICSD No.:98-009-4814

[0049] From the viewpoint of increasing the capacity of the battery and improving the power characteristics of the battery, the half-value width of the diffraction peak of the (104) plane of the X-ray diffraction spectrum based on X-ray diffraction and the crystallite size s of the lithium transition metal composite oxide calculated according to the Scherrer equation are preferably The Scherrer formula is expressed as follows: In the following formula, s is the crystallite size, λ is the wavelength of the X-ray, B is the half-value width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is set to 0.9.

[0050] s=Kλ / Bcosθ

[0051] The lithium transition metal composite oxide may have a layered structure. As the layered structure of the lithium transition metal composite oxide, for example, a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, etc. can be cited. From the viewpoint of high capacity and stability of the crystal structure, the lithium transition metal composite oxide preferably has a layered structure belonging to the space group R-3m. The layered structure of the lithium transition metal composite oxide may include a transition metal layer and a Li layer.

[0052] In the layered structure of the lithium transition metal composite oxide, the ratio of the metal elements other than Li present in the Li layer is 8 mol% or less relative to the total molar number of the metal elements other than Li in the lithium transition metal composite oxide. When the ratio of the metal elements other than Li in the Li layer exceeds 8 mol%, the diffusivity of the Li ions in the Li layer decreases, and the battery capacity sometimes decreases. The metal elements other than Li present in the Li layer are mainly Ni, but other metal elements may also be included. The ratio of the metal elements other than Li in the Li layer is, for example, 0.1 mol% or more.

[0053] The ratio of metal elements other than Li in the layered Li layer is obtained from the RietVeld analysis results of the X-ray diffraction spectrum of the lithium transition metal composite oxide based on the above X-ray diffraction measurement. For example, PDXL2 (Rigaku Corporation), which is a RietVeld analysis software, can be used for the RietVeld analysis of the X-ray diffraction spectrum.

[0054] The lithium transition metal composite oxide may include secondary particles formed by the aggregation of primary particles. The particle size of the primary particles is, for example, 0.02 μm to 2 μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle in the particle image observed by a scanning electron microscope (SEM). The average particle size of the secondary particles is, for example, 2 μm to 30 μm. Here, the average particle size refers to the median particle size (D50) based on volume. D50 refers to the particle size at which the accumulation of frequencies in the volume-based particle size distribution becomes 50% from the smaller particle size, also known as the median diameter. The particle size distribution of the secondary particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by MicrotracBEL Corp.) using water as the dispersion medium.

[0055] On the surface of the primary particles including the surface of the secondary particles, there is a surface modification layer containing at least one of Ca and Sr and P. Thus, the side reaction between the primary particles and the non-aqueous electrolyte can be significantly suppressed. The presence of Ca and P in the surface modification layer can be confirmed, for example, by energy dispersive X-ray spectroscopy (TEM-EDX).

[0056] The surface modification layer may include, for example, a compound containing at least one of Ca and Sr and a compound containing P, or may include at least one of Ca and Sr and a compound containing P. In addition, the surface modification layer may also include: a compound containing at least one of Ca and Sr, a compound containing P, a compound containing at least one of Ca and Sr, and a compound containing P. These compounds may be uniformly dispersed on the entire surface of the primary particles including the surface of the secondary particles of the lithium transition metal composite oxide, or may also be present in a part. These compounds are, for example, oxides.

[0057] At least one of Ca and Sr and P may be present in the surface modification layer and within 30 nm near the surface of the primary particle. This makes the effect of suppressing the side reaction more significant.

[0058] The positive electrode mixture layer may contain other positive electrode active materials in addition to the positive electrode active material of the present embodiment. Examples of other positive electrode active materials include lithium transition metal composite oxides that do not contain at least one of Ca and Sr and do not contain P.

[0059] Next, an example of a method for producing a positive electrode active material according to the present embodiment is described. The method for producing a positive electrode active material includes, for example, the following steps: a step of mixing a metal oxide containing at least Ni with a Li raw material, a P raw material, and at least one of a Ca raw material and a Sr raw material to obtain a mixture; and a step of calcining the mixture to obtain a positive electrode active material.

[0060] The metal oxide containing at least Ni can be prepared as follows: in a reaction tank of a solution having a pH adjusted by stirring, a solution containing a metal salt of Ni, Co, Al, Mn, etc. and an alkaline solution such as sodium hydroxide are respectively added dropwise, the pH is adjusted to alkaline (e.g., 8.5 to 12.5), so that a composite hydroxide is precipitated (coprecipitated), and the metal hydroxide is heat-treated, so that it can be prepared. The calcination temperature is not particularly limited, for example, in the range of 250° C. to 600° C.

[0061] Next, a metal oxide containing at least Ni is mixed with a Li raw material, a P raw material, a Ca raw material, and at least one of a Sr raw material to obtain a mixture. As a Li raw material, for example, Li2Co3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. can be mentioned. As a P raw material, P2O5, CaHPO4, Ca(H2PO4)2, Ca3(PO4)2, etc. can be mentioned. As a Ca raw material, Ca(OH)2, CaHPO4, Ca(H2PO4)2, Ca3(PO4)2, CaO, CaCo3, CaSO4, Ca(NO3)2, CaCl2, CaAlO4, etc. can be mentioned. Examples of Sr raw materials include Sr(OH)2, SrHPO4, Sr(H2PO4)2, Sr3(PO4)2, SrO, SrCo3, SrSO4, Sr(NO3)2, SrCl2, SrAlO4, etc. It should be noted that CaHPO4, Ca(H2PO4)2, and Ca3(PO4)2 are raw materials to which Ca and P can be added, and SrHPO4, Sr(H2PO4)2, and Sr3(PO4)2 are raw materials to which Sr and P can be added. In addition, during mixing, Me raw materials may be mixed. As Me raw materials, ZrO2, Nb2O5, Nb2O5·nH2O, TiO2, Ti(OH)4, SiO, SiO2, Li2MoO4, MoO3, H2MoO4, WO3, Li2WO4, Al(OH)2, Al2O3, Al2(SO4)3, Al(NO3) can be cited.

[0062] 3 etc.

[0063] The mixture is calcined to obtain a lithium transition metal composite oxide as a positive electrode active material. The mixture is calcined, for example, in an oxygen gas flow with an oxygen concentration of 60% or more and a flow rate of the oxygen gas flow of 10 cm / s. 3The calcination is carried out in a range of 0.1L / min to 4L / min in the calcination furnace, or at a temperature of 1L / min or more per 1kg of the mixture. Under the calcination conditions, the first set temperature is set to 450°C or less, the holding time of the first set temperature is in the range of 0 hours to 8 hours, and the heating rate below 450°C is in the range of more than 1.5°C / min and less than 6.0°C / min. The second set temperature is set to 450°C or more and 680°C or less, the holding time of the second set temperature is in the range of 0 hours to 8 hours, and the heating rate of 450°C or more and 680°C or less is in the range of more than 1.0°C / min and less than 4.5°C / min. In addition, the maximum temperature is in the range of 690°C or more and 900°C or less. The heating rate from 680°C to the maximum temperature can be, for example, 0.1°C / min to 3.5°C / min. In addition, the holding time to reach the maximum temperature can be 1 hour or more and 10 hours or less. In addition, the calcination process can be a multi-stage calcination process, as long as it is within the above-defined range, and multiple stages can be set in each temperature zone. For example, by changing the first set temperature, the second set temperature, the respective heating rates until the highest temperature is reached, and the respective holding times, the crystallinity of the lithium transition metal composite oxide changes, and the value of the half-value width ratio m / n can be adjusted.

[0064] The prepared lithium transition metal composite oxide can then be subjected to a water washing and drying process and a heat treatment process. The water washing and drying process can be carried out by known methods and conditions. It should be noted that Me raw materials can be added to the filter cake-like composition after water washing or during the heat treatment process. The heat treatment process is carried out, for example, in a vacuum, in an oxygen gas flow, in the atmosphere, at a temperature of 150°C to 600°C. As Me raw materials added after water washing or during the heat treatment process, for example, tungsten oxide (WO3), lithium tungstate (Li2WO4, Li4WO5, Li6W2O9), boric acid (H3BO3), lithium borate (Li2B4O7, Li3BO3, LiB3O5, LiBO2), aluminum oxide (Al2O3), aluminum sulfate (Al2(SO4)3), etc. can be cited.

[0065] [negative electrode]

[0066] The negative electrode 12 has, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode current collector. As the negative electrode current collector, a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode 12, a thin film having such a metal disposed on the surface layer, or the like can be used. The thickness of the negative electrode current collector is, for example, 5 μm to 30 μm. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm on one side of the negative electrode current collector. The negative electrode 12 can be produced, for example, by coating a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. on the surface of the negative electrode current collector, drying the coating film, and then performing rolling to form the negative electrode mixture layer on both sides of the negative electrode current collector.

[0067] As the negative electrode active material contained in the negative electrode mixture layer, there is no particular limitation as long as it can reversibly store and release lithium ions, and carbon materials such as graphite are usually used. The graphite can be any of natural graphite such as flake graphite, massive graphite, and earthy graphite, massive artificial graphite, graphitized mesophase carbon microbeads, and other artificial graphite. In addition, as the negative electrode active material, metals alloyed with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. can be used. In addition, those provided with a carbon coating film thereon can be used. For example, SiO x (0.5 ≤ x ≤ 1.6) of the Si-containing compound, or Li 2y SiO (2+y) (0 < y < 2) of the Si-containing compound in which fine particles of Si are dispersed in the lithium silicate phase, etc. can be used in combination with graphite.

[0068] As the binder contained in the negative electrode mixture layer, for example, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (which can be PAA-Na, PAA-K, etc., and partially neutralized salts), polyvinyl alcohol (PVA), etc. can be cited. They can be used alone or in combination of two or more.

[0069] [Separator]

[0070] In the separator 13, a porous sheet having, for example, ion permeability and insulation is used. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, etc. As the material of the separator, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can have a single-layer structure or a laminated structure. In addition, a resin layer having high heat resistance such as an aromatic polyamide resin, a filler layer containing a filler of an inorganic compound, etc. can be provided on the surface of the separator 13.

[0071] [Non-aqueous electrolyte]

[0072] The non-aqueous electrolyte contains, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of them can be used, for example. The non-aqueous solvent may contain a halogenated product obtained by substituting at least a part of the hydrogen atoms of these solvents with halogen atoms such as fluorine. Examples of the halogenated product include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated linear carbonates, and fluorinated linear carboxylates such as methyl fluoropropionate (FMP).

[0073] Examples of the above esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate; linear carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL), γ-valerolactone (GVL); and linear carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, etc.

[0074] Examples of the above ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-epoxybutane, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ethers; and linear ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.

[0075] The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3Co2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2) {l, m is an integer greater than 0} and other imide salts. The lithium salt can be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoint of ion conductivity, electrochemical stability, etc. The concentration of the lithium salt is, for example, 0.5 mol to 2 mol per 1L of the non-aqueous solvent. In addition, vinylene carbonate and propane sultone-based additives can be further added.

[0076] Example

[0077] Hereinafter, the present disclosure will be further described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.

[0078] <Example 1-1>

[0079] [Preparation of positive electrode active material]

[0080] The [Ni 0.90 Co 0.06 Mn 0.04 The composite hydroxide represented by ](OH)2 was calcined at 400°C for 8 hours to obtain a metal oxide (Ni 0.90 Co 0.06 Mn 0.04 O2). Next, the above metal oxides and CaHPO4 are mixed in such a manner that the molar ratio of Ca and P relative to the total amount of metal elements is 0.25 mol%, and further, lithium hydroxide monohydrate (LiOH·H2O) is mixed in such a manner that the molar ratio of Li relative to the total amount of Ni, Co, Mn, Ca and P is 103 mol%, to obtain a mixture. The mixture is heated from room temperature to 400°C at a heating rate of 4°C / min under an oxygen gas flow with an oxygen concentration of 95% (a flow rate of 3L / min per 1kg of the mixture), and then heated from 400°C to 650°C at a heating rate of 2°C / min. Thereafter, the temperature is raised from 650°C to 740°C at a heating rate of 1°C / min and maintained for 6 hours to obtain a lithium transition metal composite oxide. The lithium transition metal composite oxide is washed with water and dried to obtain the positive electrode active material of Example 1-1. It should be noted that, according to TEM-EDX, it was confirmed that a surface modification layer containing Ca and P existed on the surface of the positive electrode active material.

[0081] The obtained positive electrode active material was measured by an ICP emission spectrophotometer (Thermo Fisher Scientific, iCAP6300), and the elements shown in Table 1 described below were confirmed as elements other than Li and O. The half-value width ratio m / n of the positive electrode active material was 0.79. In addition, according to TEM-EDX, it can be confirmed that Ca and P are present on the surface of the primary particles including the surface of the secondary particles of the positive electrode active material.

[0082] [Production of positive electrode]

[0083] 95 parts by mass of the above-mentioned positive electrode active material are mixed with 3 parts by mass of acetylene black (AB) and 2 parts by mass of polyvinylidene fluoride (PVDF), and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is further added to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of the positive electrode collector formed by aluminum foil, and after the coating is dried, the coating is rolled using a calendering roller, cut into a specified electrode size, and a positive electrode is made. It should be noted that a portion of the positive electrode is provided with an exposed portion exposed on the surface of the positive electrode collector.

[0084] [Production of negative electrode]

[0085] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of a negative electrode collector formed of copper foil, and after the coating film is dried, the coating film is rolled using a calendering roller and cut into a specified electrode size to produce a negative electrode. It should be noted that a portion of the negative electrode is provided with an exposed portion where the surface of the negative electrode collector is exposed.

[0086] [Preparation of non-aqueous electrolyte]

[0087] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed at a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0088] [Production of test battery cells]

[0089] A positive electrode lead is installed on the exposed part of the positive electrode, and a negative electrode lead is installed on the exposed part of the negative electrode. The positive electrode and the negative electrode are wound into a spiral shape with a polyolefin separator interposed therebetween, and then press-formed in the radial direction to produce a flat wound electrode body. The electrode body is housed in an outer shell composed of an aluminum laminate sheet, and after the above-mentioned non-aqueous electrolyte is injected, the opening of the outer shell is sealed to obtain a test battery cell.

[0090] [Evaluation of heat release rate]

[0091] At an ambient temperature of 25°C, the above test battery cell was charged at a constant current of 0.3C until 4.2V, and then charged at a constant voltage of 4.2V until 0.02C was reached to form a charged state. After that, the test battery cell in the above charged state was mounted on a runaway reaction measuring device (Accelerated rate calorimeter: ARC, manufactured by Thermal Hazard Technology Co., Ltd.), and the temperature of the battery cell was observed using a thermocouple mounted on the test battery cell to measure the heat release rate (°C / minute) of the test battery cell. When no temperature rise of 0.02°C / minute or more was detected when the temperature was kept at a measurement start temperature of 80°C for 20 minutes, the ambient temperature was raised by 5°C, and the temperature was kept for another 20 minutes to measure the heat release rate. As described above, the ambient temperature was raised by 5°C at intervals until a temperature rise of 0.02°C / minute or more was detected. When a temperature rise of 0.02°C / minute or more was detected, it was determined that self-heat release had started, and the heat release rates 8 hours after the start of self-heat release were compared.

[0092] <Example 1-2>

[0093] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.92 Co 0.05 Mn 0.03 O2, and the above-mentioned metal oxide and Ca3(PO4)2 are mixed in such a manner that the molar ratio of Ca relative to the total amount of metal elements becomes 0.6 mol % and the molar ratio of P becomes 0.4 mol %. Except for this, a test battery cell is prepared and evaluated in the same manner as Example 1-1.

[0094] <Examples 1-3>

[0095] A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the positive electrode active material was prepared as follows.

[0096] (1) Changing the composition of the metal oxide to Ni 0.92 Co 0.04 Mn 0.04 O2.

[0097] (2) The above-mentioned metal oxides, CaHPO4, TiO2 and WO3 are mixed in such a manner that the molar ratios of Ca and P relative to the total amount of metal elements are 0.5 mol%, the molar ratio of Ti is 0.5 mol%, and the molar ratio of W is 0.5 mol%, respectively, to obtain a mixture.

[0098] (3) The oxygen flow rate was changed to 5 L / min per 1 kg of the mixture, and the mixture was heated from room temperature to 300°C at a heating rate of 4°C / min, then from 300°C to 550°C at a heating rate of 3°C / min, and maintained at 550°C for 4 hours. Thereafter, the mixture was heated from 550°C to 680°C at a heating rate of 3°C / min, then from 680°C to 750°C at a heating rate of 0.8°C / min, and maintained at 550°C for 6 hours, thereby obtaining a lithium transition metal composite oxide.

[0099] <Examples 1-4>

[0100] A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the positive electrode active material was prepared as follows.

[0101] (1) Changing the composition of the metal oxide to Ni 0.91 Co 0.01 Mn 0.06 Al 0.02 O2.

[0102] (2) The above-mentioned metal oxides, CaHPO4, Sr(OH)2 and SiO are mixed in such a manner that the molar ratios of Ca and P relative to the total amount of the metal elements are 1 mol %, the molar ratio of Sr is 0.5 mol %, and the molar ratio of Si is 0.5 mol %, respectively, to obtain a mixture.

[0103] (3) The mixture was heated from room temperature to 450°C at a heating rate of 4°C / min, and then maintained at 450°C for 4 hours. Thereafter, the mixture was heated from 400°C to 650°C at a heating rate of 2°C / min, and then maintained at 650°C for 2 hours. Thereafter, the mixture was heated from 650°C to 720°C at a heating rate of 1°C / min, and then maintained at 6 hours, thereby obtaining a lithium transition metal composite oxide.

[0104] <Examples 1-5>

[0105] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.90 Co 0.02 Mn 0.08 O2, and the above-mentioned metal oxides, CaHPO4, ZrO2, Nb2O5 and SiO2 are mixed in such a manner that the molar ratios of Ca and P relative to the total amount of metal elements are 0.5 mol %, the molar ratio of Zr is 0.5 mol %, the molar ratio of Nb is 0.1 mol % and the molar ratio of Si is 0.4 mol %. Except for this, a test battery cell is prepared and evaluated in the same manner as Example 1-1.

[0106] <Examples 1-6>

[0107] A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the positive electrode active material was prepared as follows.

[0108] (1) In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.91 Mn 0.07 Al 0.02 O2.

[0109] (2) The above-mentioned metal oxides, CaHPO4, Ca(OH)2 and Sr(OH)2 are mixed in such a manner that the molar ratio of Ca, the molar ratio of Sr and the molar ratio of P relative to the total amount of the metal elements become 0.6 mol %, 0.1 mol % and 0.3 mol %, respectively, to obtain a mixture.

[0110] (3) The oxygen flow rate is changed to 1 L / min per 1 kg of the mixture, and the mixture is heated from 400°C to 650°C at a heating rate of 4°C / min, maintained at 650°C for 2 hours, and then heated from 650°C to 720°C at a heating rate of 1°C / min, and maintained for 8 hours to obtain a lithium transition metal composite oxide.

[0111] <Comparative Example 1-1>

[0112] In the preparation of the positive electrode active material, the P raw material was not mixed, and the metal oxide, Ca(OH)2 and WO3 were mixed in such a way that the molar ratio of Ca relative to the total amount of the metal elements became 0.5 mol% and the molar ratio of W became 0.5 mol%. Apart from this, the test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0113] <Comparative Example 1-2>

[0114] In the preparation of the positive electrode active material, the Ca raw material was not mixed, and the metal oxide, P2O5 and Nb2O5 were mixed in such a way that the molar ratio of P relative to the total amount of the metal elements was 2 mol% and the molar ratio of Nb was 1 mol%. Apart from this, a test battery cell was prepared and evaluated in the same manner as in Example 1-1.

[0115] <Comparative Examples 1-3>

[0116] A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the positive electrode active material was prepared as follows.

[0117] (1) Changing the composition of the metal oxide to Ni 0.92 Co 0.05 Al 0.03 O2.

[0118] (2) The above-mentioned metal oxide and SrHPO4 are mixed so that the molar ratio of Sr and P to the total amount of the metal elements is 0.25 mol % respectively to obtain a mixture.

[0119] (3) The mixture was heated from room temperature to 400°C at a heating rate of 4°C / min, and then from 400°C to 650°C at a heating rate of 4.5°C / min. Thereafter, the mixture was heated from 650°C to 700°C at a heating rate of 2°C / min, and then maintained at that temperature for 4 hours to obtain a lithium transition metal composite oxide.

[0120] <Comparative Examples 1-4>

[0121] A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the positive electrode active material was prepared as follows.

[0122] (1) A metal oxide, CaHPO 4 and Sr(OH) 2 are mixed so that the molar ratio of Ca, Sr and P relative to the total amount of the metal elements is 1 mol % respectively to obtain a mixture.

[0123] (2) The temperature was raised from room temperature to 400°C at a heating rate of 4°C / min, then from 400°C to 700°C at a heating rate of 5°C / min. Thereafter, the temperature was raised from 700°C to 740°C at a heating rate of 4°C / min and maintained for 2 hours to obtain a lithium transition metal composite oxide.

[0124] <Example 2-1>

[0125] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.80 Co 0.10 Mn 0.10 O2, the above-mentioned metal oxides, Ca(H2PO4)2 and SrHPO4 were mixed in such a manner that the molar ratio of Ca, the molar ratio of Sr and the molar ratio of P relative to the total amount of metal elements became 0.5 mol %, 0.25 mol % and 1.25 mol %, and the temperature was increased from 650°C to 800°C at a heating rate of 1°C / min and then maintained for 10 hours. Except for this, a test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0126] <Comparative Example 2-1>

[0127] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.80 Co 0.10 Mn 0.10O2, without mixing and sintering with the Ca raw material and the P raw material, using the above-mentioned metal oxide as the positive electrode active material, and heating from 650°C to 760°C at a heating rate of 1°C / min and then maintaining for 10 hours. Except for this, a test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0128] <Comparative Example 2-2>

[0129] In the preparation of the positive electrode active material, the composition of the metal oxide is changed to Ni 0.83 Co 0.12 Mn 0.05 O2, the above-mentioned metal oxides and SrHPO4 were mixed in such a manner that the molar ratios of Sr and P relative to the total amount of metal elements were each 0.75 mol%, and the temperature was raised from 650°C to 800°C at a heating rate of 1°C / min and then maintained for 10 hours. Except for this, a test battery cell was prepared and evaluated in the same manner as Example 1-1.

[0130] The evaluation results of the test battery cells of the embodiments and comparative examples are shown in Tables 1 and 2. In addition, Tables 1 and 2 also show the composition of the positive electrode active material, the total of the Ca content and the Sr content, the ratio of the Co content to the Mn content, the half-value width ratio m / n, the ratio of metal elements other than Li in the Li layer, and the crystallite size s. In Table 1, the heat release rate of the test battery cells other than Comparative Example 1-1 is relatively expressed by setting the heat release rate of the test battery cell of Comparative Example 1-1 to ±0. In addition, in Table 2, the heat release rate of the test battery cells other than Comparative Example 2-1 is relatively expressed by setting the heat release rate of the test battery cell of Comparative Example 2-1 to ±0.

[0131] [Table 1]

[0132]

[0133] [Table 2]

[0134]

[0135] In Table 1 and Table 2, the heat release rate of the test battery cells of the examples is lower than that of the test battery cells of the comparative examples. From this, it can be known that by including a lithium transition metal composite oxide in the positive electrode active material, which contains Ni, Mn, P, Me (Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W, and Bi) at a specified content rate, and contains at least any one of Ca and Sr, and the ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (110) plane in the X-ray diffraction spectrum based on X-ray diffraction is 0.75 ≤ m / n, the safety of the secondary battery is improved.

[0136] The present disclosure will be further described according to the following embodiments.

[0137] Configuration 1:

[0138] A positive electrode active material for a non-aqueous electrolyte secondary battery, which contains a lithium transition metal composite oxide,

[0139] The aforementioned lithium transition metal composite oxide contains Ni, Mn, P, Me (Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W, and Bi), and contains at least any one of Ca and Sr,

[0140] The Ni content rate in the aforementioned lithium transition metal composite oxide is 75 mol% ≤ Ni content rate ≤ 95 mol% relative to the total molar amount of metal elements other than Li,

[0141] The Mn content rate in the aforementioned lithium transition metal composite oxide is 0 mol% < Mn content rate ≤ 20 mol% relative to the total molar amount of metal elements other than Li,

[0142] The P content rate in the aforementioned lithium transition metal composite oxide is 0 mol% < P content rate ≤ 2 mol% relative to the total molar amount of metal elements other than Li,

[0143] The Me content rate in the aforementioned lithium transition metal composite oxide is 0 mol% < Me content rate ≤ 20 mol% relative to the total molar amount of metal elements other than Li,

[0144] The total of the Ca content rate and the Sr content rate in the aforementioned lithium transition metal composite oxide is 0 mol% < Ca content rate + Sr content rate ≤ 2 mol% relative to the total molar amount of metal elements other than Li,

[0145] The ratio of the Co content rate to the aforementioned Mn content rate is 0 ≤ Co content rate / Mn content rate < 2,

[0146] The ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (110) plane in the X-ray diffraction spectrum based on X-ray diffraction is 0.75≤m / n.

[0147] Composition 2:

[0148] The positive electrode active material for a non-aqueous electrolyte secondary battery according to configuration 1, wherein

[0149] The lithium transition metal composite oxide has a layered structure.

[0150] The ratio of the metal element other than Li present in the Li layer of the layered structure is 8 mol% or less relative to the total number of moles of the metal element other than Li in the lithium transition metal composite oxide.

[0151] Composition 3:

[0152] According to the positive electrode active material for a non-aqueous electrolyte secondary battery as described in configuration 1 or 2, the crystallite size s of the lithium transition metal composite oxide calculated from the half-value width of the diffraction peak of the (104) plane of the X-ray diffraction spectrum based on X-ray diffraction and the Scherrer equation is

[0153] Composition 4:

[0154] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the lithium-transition metal composite oxide includes secondary particles formed by aggregation of primary particles,

[0155] A surface modification layer containing at least one of Ca and Sr and P exists on the surface of the primary particle including the surface of the secondary particle.

[0156] Composition 5:

[0157] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the lithium-transition metal composite oxide contains both Ca and Sr.

[0158] Composition 6:

[0159] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the Ca content > the Sr content is satisfied.

[0160] Composition 7:

[0161] A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery comprises the following steps:

[0162] A step of mixing a metal oxide containing at least Ni with a Li raw material, a P raw material, and at least one of a Ca raw material and a Sr raw material to obtain a mixture; and,

[0163] The mixture is then calcined.

[0164] Composition 8:

[0165] A nonaqueous electrolyte secondary battery comprising: a positive electrode including the positive electrode active material for a nonaqueous electrolyte secondary battery according to any one of configurations 1 to 6; a negative electrode; and a nonaqueous electrolyte.

[0166] Description of Reference Numerals

[0167] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer shell, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, which comprises a lithium transition metal composite oxide, the lithium transition metal composite oxide contains Ni, Mn, P, Me, and contains at least one of Ca and Sr, and Me is at least one element selected from the group consisting of B, Al, Si, Ti, Fe, Co, Sr, Zr, Nb, Mo, Sn, W, and Bi, the Ni content rate in the lithium transition metal composite oxide is 75 mol% ≤ Ni content rate ≤ 95 mol% with respect to the total molar number of metal elements other than Li, the Mn content rate in the lithium transition metal composite oxide is 0 mol% < Mn content rate ≤ 20 mol% with respect to the total molar number of metal elements other than Li, the P content rate in the lithium transition metal composite oxide is 0 mol% < P content rate ≤ 2 mol% with respect to the total molar number of metal elements other than Li, the Me content rate in the lithium transition metal composite oxide is 0 mol% < Me content rate ≤ 20 mol% with respect to the total molar number of metal elements other than Li, the total of the Ca content rate and the Sr content rate in the lithium transition metal composite oxide is 0 mol% < Ca content rate + Sr content rate ≤ 2 mol% with respect to the total molar number of metal elements other than Li, the ratio of the Co content rate to the Mn content rate is 0 ≤ Co content rate / Mn content rate < 2, the ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (110) plane in the X-ray diffraction pattern based on X-ray diffraction is 0.75 ≤ m / n.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, the lithium transition metal composite oxide has a layered structure, the ratio of metal elements other than Li present in the Li layer of the layered structure is 8 mol% or less with respect to the total molar number of metal elements other than Li in the lithium transition metal composite oxide.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the crystallite size s of the lithium transition metal composite oxide calculated from the half width of the diffraction peak of the (104) plane of the X-ray diffraction spectrum based on X-ray diffraction is 4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein, the lithium transition metal composite oxide contains secondary particles formed by aggregation of primary particles, a surface modification layer containing at least one of Ca and Sr and containing P exists on the surface of the primary particles including the surface of the secondary particles.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide contains both Ca and Sr.

6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, which satisfies the Ca content rate > the Sr content rate.

7. A method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery, which includes the following steps: a step of mixing a metal oxide containing at least Ni with a Li raw material, a P raw material, and at least one of a Ca raw material and an Sr raw material to obtain a mixture; and, a step of firing the mixture.

8. A non-aqueous electrolyte secondary battery, which includes: a positive electrode, a negative electrode, and a non-aqueous electrolyte, the positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 6.